A business plan of Kalakalang kape Kobing Company for micro scale production of civet coffee green beans - Catingub, Wilson Bustamante, Jr. (2011)
Kalakalang Kape Kobing (3K) company is a business entity solely-owned and managed by Mr. Wilson B. Catingub, Jr. The organization concentrates on the micro scale production of green civet coffee beans to directly supply the coffeehouses in Davao City. Its processing plant is situated in Digos City, Davao del Sur where the raw civet coffee beans are polished, stringently quality controlled and packaged in a specialized coffee packaging material with moisture barrier and approximately designed for maximum consumer appeal. With this packaging, the product can be stored for 2 years. To start-up the business, the company requires a capital of Php300,000.00. This will be used for securing the business's legal requirements, processing plant renovation, procurement of raw materials and equipment, salary of employees and other expenses necessary to operate the business. The Php250,000.00 of the capital will be loaned from the GSIS while the remaining Php50,000.00 will be from the personal savings of the owner. Projecting the business performance for 5 years, the company has the following financial ratios which measure the profitability of the company: Return of Investment (ROI) for the first year of operation is 80% and 295% after 5 years. ; Net profit Margin (NPM) of 18% on the first year and 31% after 5 years; and the Return on Sales (ROS) is 42% on the first year and 53% after 5 years. Referring to these ratios, the business on micro scale production of green civet coffee beans can be considered profitable and promising.
Thesis (BS Food Technology) -- University of the Philippines Mindanao, 2011
Keywords: Kalakalang Kape Kobing (3K) Company; Coffee; Green civet coffee beans; Coffeehouses; Processing plant -- Digos City, Davao del Sur; Return on Investment (RO); Micro-scale production; Net Profit Margin (NPM).; Coffee packaging material; Return on Sales (ROS).; Coffee industry -- Davao City -- Philippines